2021
DOI: 10.3390/molecules26092636
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenous Compounds from the Antarctic Fungus Pseudogymnoascus sp. HSX2#-11

Abstract: The species Pseudogymnoascus is known as a psychrophilic pathogenic fungus which is ubiquitously distributed in Antarctica. While the studies of its secondary metabolites are infrequent. Systematic research of the metabolites of the Antarctic fungus Pseudogymnoascus sp. HSX2#-11 led to the isolation of one new pyridine derivative, 4-(2-methoxycarbonyl-ethyl)-pyridine-2-carboxylic acid methyl ester (1), together with one pyrimidine, thymine (2), and eight diketopiperazines, cyclo-(dehydroAla-l-Val) (3), cyclo-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The reason may be the degradation of the sampled grassland soils. Pseudogymnoascus belongs to cold-tolerant fungi, which are more suitable for survival in alpine environments ( Shi et al, 2021 ), which explains why he relative abundance of Pseudogymnoascus was the highest in temperate steppe-sandy soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason may be the degradation of the sampled grassland soils. Pseudogymnoascus belongs to cold-tolerant fungi, which are more suitable for survival in alpine environments ( Shi et al, 2021 ), which explains why he relative abundance of Pseudogymnoascus was the highest in temperate steppe-sandy soil.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be the degradation of the sampled grassland soils. Pseudogymnoascus belongs to cold-tolerant fungi, which are more suitable for survival in alpine environments (Shi et al, 2021), which explains why he relative abundance of Pseudogymnoascus was the highest in temperate steppe-sandy soil. Meanwhile, the more connections in the soil microbial community network, the higher its stability and the stronger the ability to inhibit the invasion of pathogens (Shi et al, 2016;Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Fungi from the genus Pseudogymnoascus exhibit interesting capabilities in their specialized metabolism [15][16][17][18][19][20][21]. To gain a deeper understanding of Pseudogymnoascus' metabolic potential, molecular tools enabling its genetic manipulation are essential.…”
Section: Discussionmentioning
confidence: 99%
“…From a biotechnological perspective, numerous studies have demonstrated that extracts derived from diverse strains of Pseudogymnoascus harbor bioactive metabolites with antibacterial, antifungal, trypanocidal, herbicidal, and antitumoral properties [9][10][11][12][13][14]. Furthermore, chemical analyses of Pseudogymnoascus strains have revealed that members of this fungal genus produce different classes of compounds, such as sesquiterpenes [15], macrolides [16], polyketides [17,18], tetrapeptides [19], and various nitrogenous compounds [20,21]. This underscores the potential of Pseudogymnoascus as a prolific source of specialized metabolites.…”
Section: Introductionmentioning
confidence: 99%